Trainee wellness: self-critical perfectionism, self-compassion, depression, and burnout among doctoral trainees in psychology. Issue 2 (2nd April 2020) - Richardson, Clarissa M. E.; Trusty, Wilson T.; George, Kylie A.
ABSTRACT: Training to become a therapist is a uniquely challenging process with frequent evaluation and balancing of multiple roles (e.g. student, teacher, researcher, counselor, and supervisee). In fact, studies report high levels of stress and depression among graduate trainees in psychology. These vulnerabilities can be exacerbated when a trainee is in high in self-critical perfectionism, a feeling that one is never good enough. The present study examines associations between self-critical perfectionism, depression, and burnout among doctoral trainees in psychology, investigating the mediating role of self-compassion. The 119 participants were all students in clinical/counseling psychology doctoral programs. Results indicated that those higher in self-critical perfectionism reported higher levels of depression and burnout. Self-compassion partially mediated the relationship between self-critical perfectionism and depression, and burnout; those higher in self-compassion experienced lower levels of depression and burnout. These results point to the importance of facilitating the development of self-compassion among doctoral trainees, specifically those who are high in self-critical perfectionism.